Contemporary Challenges to the Concept of Nikah and Divorce in Pakistan: Critical Discourse of Judicial Activism and Religious Scholars Viewpoint - Dr. Akbar Ali,; Dr. Bashir Ahmad,; Dr. Nasim Hayat,; Dr. Anwarullah,; Dr. Sardar Ali, (Al-Qanṭara, 2024)
Family is the cornerstone of a peaceful society, and Nikah is the rightful way of constituting a family. Marriage and divorce in Pakistan are currently facing issues that have led to significant discussions, especially over judicial activity and the viewpoints of religious academics. This study examines the complex difficulties by analyzing the interaction between legal systems and religious interpretations. Judicial activism in Pakistan has significantly influenced the definition of Marriage and divorce. Courts are more frequently involved in resolving matters concerning women's rights, gender equality, and safeguarding individual freedoms under Islamic law. This involvement has sparked discussions among legal experts and religious leaders, influencing the changing field of family law. Religious experts are dealing with the conflicts between traditional interpretations of Islamic law and the changing social dynamics in present-day Pakistan. The study analyses different perspectives within religious communities about topics including women's rights in Marriage, reasons for divorce, and the influence of religious beliefs on family law. This critical discourse explores the complexity of Nikah and divorce in Pakistan, focusing on the interplay between legislative reforms, judicial activity, and religious factors.